Prinsip Akuntabilitas dan Partisipasi dalam Pengelolaan Dana Desa di Desa Buncu Kecamatan Sape Kabupaten Bima - Imaduddin, Imaduddin; Salomo, Roy Valiant (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This study aims to analyze the principles of good governance in managing the 2022 Village Fund in Buncu Village, Sape District, Bima Regency. Researchers use Buncu Village because it has the status of an underdeveloped village category with a developing village index of 0.5776. In addition, this village is unable to achieve the realization of Village Funds in 2022. This research focuses more on two important principles based on the factual problems found, namely the principle of accountability and the principle of community participation. The research method used in this research uses descriptive qualitative research. Data collection techniques are carried out by conducting documentation studies and. The results of this study indicate that accountability in managing Village Funds in Buncu Village is not in accordance with Permendagri No. 20 of 2018 concerning reporting and accountability mechanisms, but in general it has been carried out properly. In terms of the principle of planning participation, the Buncu Village Government has also implemented the principle of participation because every RKPDes preparation always involves the community. In addition, in terms of implementing participation, the people of Buncu Village are voluntarily involved in village development.